2015
DOI: 10.1016/j.psyneuen.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Blunted endocrine and cardiovascular reactivity in young healthy women reporting a history of childhood adversity

Abstract: ACEs are associated with blunted endocrine and cardiovascular stress reactivity in young and healthy women. Adverse life events in childhood, particularly if they occur repeatedly and chronically, show a strong association with alterations in stress reactivity in adulthood, potentially predisposing for later mental or physical disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
68
2
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 61 publications
18
68
2
9
Order By: Relevance
“…At this point, a normalization of CRH results in diminished adrenocorticotropin hormone (ACTH) secretion, and ultimately produces cortisol levels below the normal baseline. Importantly, this model corresponds with studies that have demonstrated age at traumatization to be an important factor for cortisol reactivity (e.g., Bosch et al, 2012;Voellmin et al, 2015).…”
Section: The Role Of Hpa Axis Functioningsupporting
confidence: 81%
“…At this point, a normalization of CRH results in diminished adrenocorticotropin hormone (ACTH) secretion, and ultimately produces cortisol levels below the normal baseline. Importantly, this model corresponds with studies that have demonstrated age at traumatization to be an important factor for cortisol reactivity (e.g., Bosch et al, 2012;Voellmin et al, 2015).…”
Section: The Role Of Hpa Axis Functioningsupporting
confidence: 81%
“…For example, the anti-inflammatory and glucose metabolism functions of cortisol may leave the low-cortisol individual at heightened risk for immune and insulin-related health problems (Miller, Cohen, & Ritchey, 2002; Raison & Miller, 2003). Importantly, this calibration of the body’s stress response system is in response to the individual’s social environment and stressor exposure (Voellmin et al, 2015), calling attention to the importance of social determinants of health particularly within the African American community.…”
Section: Discussionmentioning
confidence: 99%
“…Those who have experienced ACEs show an exaggerated inflammatory response to acute laboratory stress (Trier Social Stress Test; TSST) (Carpenter et al, 2010), larger IL-6 response to daily stressors (Gouin et al, 2012), and larger ex vivo cytokine responses to microbial challenge or lipopolysaccharide (LPS) stimulation (Miller et al, 2011) compared with those without a history of childhood adversity. Individuals with exposure to childhood adversity also evidence dysregulated HPA axis function (Bunea et al, 2017), including blunted cortisol response to the TSST or Montreal Imaging Stress Task (MIST) (Carpenter et al, 2007; Lovallo, 2013; Suzuki et al, 2014; Voellmin et al, 2015), blunted cortisol awakening response (CAR) (Kumsta et al, 2017), greater heterogeneity in diurnal cortisol patterns (Gonzalez et al, 2009), low hair cortisol (Kalmakis et al, 2015), and blunted cortisol response to a separation stressor at six months postpartum (Morrison et al, 2017). During pregnancy specifically, high ACE women show lower baseline cortisol (Shea et al, 2007), greater hair cortisol levels (Schreier et al, 2015), increased cortisol response to daily stress (Bublitz and Stroud, 2012), elevated CAR in the context of poor current perceived family function (Bublitz et al, 2014), and greater hair cortisol associated with depressive or somatic symptoms (Bowers et al, 2018).…”
Section: Introductionmentioning
confidence: 99%